Role of Azithromycin in Enteric Fever - Muhammad Sabir; Babar, Habib Ullah; Ahmed, Saboor; Kakar, Asfand Yar; Muhammad Shoaib; Imtiaz Hashim, Imtiaz; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: In low- and middle-income nations, particularly in South Asia, where growing resistance to first-line and fluoroquinolone antibiotics has made treatment more difficult, enteric (typhoid) fever continues to be a serious public health concern. An alternate therapy option that has showed potential is azithromycin, an oral macrolide antibiotic. Nevertheless, there is a dearth of local data assessing its therapeutic effectiveness, especially in young patients. Objective: The purpose of this study was to assess azithromycin's clinical results, safety, and tolerability in treating pediatric patients (ages 2–12) with enteric fever in a local healthcare facility. Methods: Over the course of six months, 121 pediatric children receiving azithromycin for clinically confirmed enteric fever participated in a cross-sectional, qualitative study. Structured interviews were used to gather clinical data, which were then backed up by TyphiDot or other lab testing. Defervescence time, clinical improvement by Day 7, and side effects were important end indicators. Results: Of the 121 patients, 86.8% attained defervescence in five days, and 85.1% demonstrated clinical improvement by Day 7. 83.5% of patients reported no side effects from azithromycin, indicating that medication was well tolerated. The most frequent adverse effects, which included nausea (8.3%) and abdominal pain (5%), were minor and self-limiting. Treatment success was positively connected with positive TyphiDot (IgM or IgM+IgG), while positive responses were seen even in clinically diagnosed individuals without confirming testing. Conclusion: For pediatric enteric fever, azithromycin is a safe, well-tolerated, and clinically effective oral antibiotic that provides a useful substitute in outpatient and resource-constrained settings. These results provide credence to its inclusion in regional therapy protocols. It is advised that research that is more extensive be done to validate these findings and guide national policy.